Pengaruh Pengetahuan, Sikap dan Motivasi Terhadap Kepatuhan Dokter dalam Penulisan Diagnosis pada Resume Medis di RS Zahirah 2018 - Husni, Muhammad (UI Scholars Hub, 2018)
The writing of a diagnosis on medical resume is the responsibility of the physician in charge of the patient (DPJP), for the benefit of BPJS claims. This relates to doctors' compliance in the diagnosis of medical resumes. Knowledge, attitudes, and motivations affect the physician's neck in writing the diagnosis on medical resume. This study aims to determine the influence of knowledge, attitudes, and motivation either partially or simultaneously to the doctor's compliance in the writing of the diagnosis on medical resume at Zahirah Hospital in 2018. This research is quantitative analytic, with cross sectional and prospective approach. The results showed that knowledge had no significant effect on the adherence of the diagnosis on the patient's medical resume (p value 0.091; R2 0.113). However, attitudes and motivations positively and positively affect the adherence of diagnosis to the patient's medical records (p value 0,000 and 0,000; R2 0,562 and 0.574). Knowledge, attitudes and motivations jointly affect the compliance (p value 0,000; R2 0.679). Zahirah Hospital should continue to support the work environment in the hospital so that doctors' compliance in writing disease diagnosis on the patient's medical resume increases. Doctors at Zahirah Hospital should be able to write medical diagnoses on medical resumes on time.